Randomised trial of oral and intravenous methylprednisolone in acute relapses of multiple sclerosis. - Barnes, D; Hughes, R; Morris, R; Wade-Jones, O; Brown, P; Britton, T; Francis, D; Perkin, G; Rudge, P; Swash, M; Katifi, H; Farmer, S; et al. (1997)
BACKGROUND: An intravenous rather than oral course of methylprednisolone is often prescribed for treating acute relapses in multiple sclerosis (MS) despite the lack of evidence to support this route of administration. Our double-blind placebo-controlled randomised trial was designed to compare the efficacy of commonly used intravenous and oral steroid regimens in promoting recovery from acute relapses in MS. METHODS: 42 patients with clinically definite relapse in MS received oral, and 38 intravenous, methylprednisolone. Clinical measurements at entry and at 1 week, 4 weeks, 12 weeks, and 24 weeks included Kurtzke's expanded disability status scale (EDSS), Hauser's Ambulatory Index, and an arm-function index. The primary outcome criterion was a difference between the two treatment groups of one or more EDSS grades at 4 weeks. FINDINGS: There were no significant differences between the two groups at any stage of the study in any measurement taken: the mean difference in EDSS at 4 weeks (adjusted for baseline level) was 0.07 grades more in those taking oral steroids (95% CI -0.46 to 0.60). The most optimistic outcome for intravenous therapy is an average benefit of less than half a grade improvement on EDSS over oral treatment. INTERPRETATION: Since our study did not show any clear advantage of the intravenous regime we conclude that it is preferable to prescribe oral rather than intravenous steroids for acute relapses in MS for reasons of patient convenience, safety, and cost.